Educationional health for pregnant women using the group strategy - Vasconcelos, Camila Teixeira Moreira; Machado, Maria de Fátima Antero Sousa; Becker, Samélia Léa Menezes (Rev Rene, 2007)
Among the several tools available to the primary health care professionals, the group strategy has been very encouraged and pregnancy has been a unique opportunity for the implementation of educational actions like these. This study consists of the report of experience about the use of this strategy including primary care pregnant women of the main focus of health promotion. It is evident that the group facilitates the educational process, when it is based on the principles of health promotion, allowing exchange of data and experiences, development of autonomy and adoption of healthy habits. Besides, this research was an activity evaluated positively by the participants because, from the information collected and the applied methodology, they felt safer, confident to play the role of mother. We hope, with this study, to encourage other professionals to use this health education tool to improve the quality of health assistance offered to the women.